2002
DOI: 10.1143/jjap.41.6049
|View full text |Cite
|
Sign up to set email alerts
|

Low Temperature Sintering and Microwave Dielectric Properties of Ba2Ti9O20Ceramics with 3ZnO–B2O3Addition

Abstract: Boron and zinc oxide (ZnBO) glass added in dielectric materials have drawn a great attention recently due to the low firing temperature. Microwave dielectric properties of the Ba 2 Ti 9 O 20 -based ceramics with ZnBO addition up to 3 wt% were investigated at the sintering temperatures ranging from 900 to 960 C. Effects of the ZnBO addition on the bulk density, microstructure, and dielectric properties of the Ba 2 Ti 9 O 20 -based ceramics at microwave frequency were elucidated. X-ray diffraction (XRD) results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 5 publications
0
19
0
Order By: Relevance
“…The pure Ba 2 Ti 9 O 20 phase was obtained at the low temperature of 900 • C because the eutectic reaction could increase the volume of liquid phase and accelerate the migration of reactant species through the liquid phase formed between the grains in the pellet. Lee et al reported that pure Ba 2 Ti 9 O 20 was obtained by use 3ZnO-B 2 O 3 [12]. B 2 O 3 was dissolved in acetic acid to formed solution at first, and then added it to Ba-Ti-solution.…”
Section: Methodsmentioning
confidence: 99%
“…The pure Ba 2 Ti 9 O 20 phase was obtained at the low temperature of 900 • C because the eutectic reaction could increase the volume of liquid phase and accelerate the migration of reactant species through the liquid phase formed between the grains in the pellet. Lee et al reported that pure Ba 2 Ti 9 O 20 was obtained by use 3ZnO-B 2 O 3 [12]. B 2 O 3 was dissolved in acetic acid to formed solution at first, and then added it to Ba-Ti-solution.…”
Section: Methodsmentioning
confidence: 99%
“…The glass from the ZnO-B 2 O 3 system is a material with low melting point, and has already had many important applications as a good sintering agent in LTCC technique [1][2][3]. According to our recent work, the addition of V 2 O 5 to ZnO-B 2 O 3 glasses can significantly improve the sintering behavior of the glass, which could be of great interest in industry application.…”
Section: Introductionmentioning
confidence: 94%
“…Reni Iordanova et al [4] studied the structure of B 2 O 3 -V 2 O 5 glasses by IR spectroscopy. They found that the glasses rich in V 2 in particular, the structure of the glass with low V 2 O 5 content has never been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, 14) we have investigated the microwave dielectric properties of the Ba2Ti9O20 ceramics with different addition amounts of 3 ZnO-B2O3 (ZnBO). The results indicate that the addition of ZnBO in the Ba2Ti9O20-based ceramics can effectively lower the sintering temperature to ~940°C, and increases the apparent density and dielectric constant of the sintered ceramics.…”
Section: Resultsmentioning
confidence: 99%